Nonlinear Dynamic Constitutive Model of Frozen Sandstone Based on Weibull Distribution - Lei Wang; Hongming Su; Shiguan Chen; Yue Qin (Advances in Civil Engineering)
To obtain the dynamic mechanical properties of frozen sandstone at different temperatures (i.e., 20°C, −10°C, −20°C, and −30°C), dynamic uniaxial compression tests of saturated sandstone are conducted using a split-Hopkinson pressure bar. The experimental results demonstrated that the brittleness of the saturated sandstone increased and its plasticity weakened with a decrease in temperature. The peak strength and dynamic elastic modulus of the sandstone were positively correlated with its strain rate. The peak stress was most sensitive to the strain rate at −10°C, and the elastic modulus was most sensitive to the strain rate at −30°C. According to the evident segmentation characteristics of the obtained stress-strain curve, a viscoelastic dynamic constitutive model considering the strain rate effect and temperature effect is developed; this model combines a nonlinear (or linear) body and a Maxwell body in parallel with a damage body. The applicability of the constitutive model is also verified using experimental data. The fitting results were demonstrated to be in good agreement with the experimental results. Furthermore, the fitting results serve as reference for the study of the constitutive model of weakly cemented soft rock and the construction of roadway freezing methods.